Analysis of the Effect of a Glass Layer on the Roof of a House of a Thermoelectric Generator on Temperature and Electrical Voltage - Aprizal Saputra; Remon Lapisa; Refdinal Refdinal; Sri Rizki Putri Primandari (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2022)
Utilization of solar power can use a thermoelectric generator. Thermoelectric Generators work by taking advantage of temperature differences and the application of the Seebeck effect. This experimental study uses two prototypes of a perfect house with a roof made of zinc plate. One of the roofs of the house is covered with glass. Thermoelectrics are installed at the bottom of the roof of each house as many as 12 pieces and arranged in a series circuit. Data collection was carried out one day from 08.00 -15.59. The largest electrical voltage obtained occurred at 11.00 – 13.59 reaching 0.215 – 0.183 Volts in houses with glass-covered roofs and 0.654 – 0.527 Volts. The use of a layer of glass makes the roof temperature stable because the heat absorbed can be retained by the glass. As a result, the voltage generated in a house with a glazed roof is more stable than a house with a non-glazed roof. This research also proves that the difference in temperature affects the voltage generated by the thermoelectric. Pemanfaatan tenaga surya dapat menggunakan termoelektrik generator. Termoelektrik Generator bekerja dengan memanfaatkan perbedaan temperatur dan penerapan efek Seebeck. Penelitian eksperimen ini menggunakan dua prototipe rumah sempurna dengan atap dari seng plat. Salah satu atap rumah dilapisi dengan kaca. Termoelektrik dipasang pada bagian bawah atap masing-masing rumah sebanyak 12 buah dan disusun dengan rangkaian seri. Pengambilan data dilakukan satu hari dari pukul 08.00 -15.59. Tegangan listrik terbesar yang didapatkan terjadi pada pukul 11.00 – 13.59 mencapai 0,215 – 0,183 Volt pada rumah dengan atap dilapisi kaca dan 0,654 – 0,527 Volt. Penggunaan lapisan kaca membuat temperatur atap menjadi stabil karena panas yang diserap dapat ditahan oleh kaca. Akibatnya membuat tegangan yang dihasilkan pada rumah dengan atap dilapisi kaca lebih stabil. Dari penelitian ini juga membuktikan perbedaan temperatur mempengaruhi tegangan listrik yang dihasilkan oleh termoelektrik.